Degradation of resin-dentin bonds of etch-and-rinse adhesive system to primary and permanent teeth - Tathiane Larissa Lenzi; Fabio Zovico Maxnuck Soares; Rachel de Oliveira Rocha (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of this in vitro study was to compare the degradation of resin-dentin bonds of an etch-and-rinse adhesive system to primary and permanent teeth. Flat superficial coronal dentin surfaces from 5 primary second molars and 5 permanent third molars were etched with phosphoric acid and bonded with an adhesive system (Adper Single Bond 2, 3M ESPE). Blocks of resin composite (Z250, 3M ESPE) were built up and the teeth sectioned to produce bonded sticks with a 0.8 mm² cross-sectional area. The sticks of each tooth were randomly divided and assigned to be subjected to microtensile testing immediately (24 h) or after aging by water storage (6 months). Data were analyzed by two-way repeated measures ANOVA and Tukey post hoc test (α = 0.05). Failure mode was evaluated using a stereomicroscope (400×). Microtensile values significantly decreased after the 6 months aging, independent of the dentin substrate. In 24 h, the values obtained to primary dentin were lower compared with permanent dentin. This difference was not maintained after aging. Adhesive/mixed failure was predominant in all experimental groups. In conclusion, degradation of resin-dentin bonds of the etch-and-rinse adhesive system occurred after 6 months of water storage; however, the reduction in bond strength values was higher for permanent teeth.